Advances in biological functions and mechanisms of histone variants in plants - Wu, Xi; Zhang, Xu; Huang, Borong; Han, Junyou; Fang, Huihui (Frontiers in Genetics, 2023)
Nucleosome is the basic subunit of chromatin, consisting of approximately 147bp DNA wrapped around a histone octamer, containing two copies of H2A, H2B, H3 and H4. A linker histone H1 can bind nucleosomes through its conserved GH1 domain, which may promote chromatin folding into higher-order structures. Therefore, the complexity of histones acts importantly for specifying chromatin and gene activities. Histone variants, encoded by separate genes and characterized by only a few amino acids differences, can affect nucleosome packaging and stability, and then modify the chromatin properties. Serving as carriers of pivotal genetic and epigenetic information, histone variants have profound significance in regulating plant growth and development, response to both biotic and abiotic stresses. At present, the biological functions of histone variants in plant have become a research hotspot. Here, we summarize recent researches on the biological functions, molecular chaperons and regulatory mechanisms of histone variants in plant, and propose some novel research directions for further study of plant histone variants research field. Our study will provide some basis for studying and understanding the epigenetic regulation and chromatin specialization mediated by histone variant in plant.